Health and Safety Law from the Industrial Revolution to the New Zealand Health and Safety at Work Act 2015 - Brabant, DeAnne (New Zealand Journal of Health and Safety Practice, 2024)
This article reviews the development of work health and safety legislation from the late 18th century to the New Zealand Health and Safety at Work Act 2015.